Nanostructure and functional group engineering of black phosphorus via plasma treatment for CO2 photoreduction. Issue 54 (December 2021) - Zhu, Xingwang; Zhou, Guli; Wang, Zhaolong; Zhong, Kang; Ding, Penghui; Song, Yanhua; Yuan, Junjie; She, Yuanbin; Li, Huaming; Xu, Hui
Highlights: The NH3 low-temperature plasma in situ exfoliation strategy was revealed. Abundant active sites and low CO2 activation energy barriers provide a hotbed. Plasma exfoliation strategy has great potential to replace traditional LPE ways. Abstract: As an emerging two-dimensional (2D) semiconductor, black phosphorus (BP) has attracted great interest in photocatalytic CO2 reduction, but the performance is restricted by the low surface reactivity and poor stability. Exfoliating BP into the 2D structure is an effective method to increase the exposure of active sites. However, the intrinsic surface reactivity and stability cannot be improved, and, the widely used liquid-phase exfoliation method is time-consuming and laborious. In this work, we successfully exfoliates the bulk BP into ultrathin BP nanosheets with dense surface amino-functional groups (BP-NH2 ) using NH3 plasma treatment. The 2D structure can shorten the photo-excited charges migration distance and improve the exposure of surface-active sites. Furthermore, the amino-functional groups on ultrathin BP nanosheets can prevent the destruction of BP nanosheets in ambient air, favoring the charge separation, CO2 adsorption and activation during the catalytic process. Benefiting from integrated advantages of amino functional groups, the optimal BP-NH2 exhibits a photocatalytic CO2 reduction rate to CO of 27.6 μmol g −1 h −1 with a selectivity of 87.0 %, both of which are higher than those of pristine bulk BP. This work presents ideas for stabilizing BP and improving the CO2 reduction performance simultaneously.